Public relations : the profession and the practice - Lattimore, Dan (McGraw-Hill, 2012)
"Public relations has developed as a major force in a growing, global information society. The practice of public relations is changing to include new, interactive media, while continuing to depend on the foundation of traditional media. The multi-disciplinary approach to understanding public relations is provided by the authors who come from business, journalism, communication and advertising backgrounds. The easy-to-read style of the text has been a hallmark of the text from its beginning. It includes spotlights on important topics or issues, mini-cases with short real-life cases, and end-of-the-chapter case studies often of major events such as the BP crisis, or GM's financial crisis where it used social media to provide interactive relationships with its constituencies"